Randomized clinical trial of brewed green and black tea in men with prostate cancer prior to prostatectomy. Issue 5 (24th December 2014) - Henning, Susanne M.; Wang, Piwen; Said, Jonathan W.; Huang, Min; Grogan, Tristan; Elashoff, David; Carpenter, Catherine L.; Heber, David; Aronson, William J.
<x xml:space="preserve">Abstract</x> Background Preclinical and epidemiologic studies suggest chemopreventive effects of green tea (GT) and black tea (BT) in prostate cancer. In the current study we determined the effect of GT and BT consumption on biomarkers related to prostate cancer development and progression. Methods In this exploratory, open label, phase II trial 113 men diagnosed with prostate cancer were randomized to consume six cups daily of brewed GT, BT or water (control) prior to radical prostatectomy (RP). The primary endpoint was prostate tumor markers of cancer development and progression determined by tissue immunostaining of proliferation (Ki67), apoptosis (Bcl‐2, Bax, Tunel), inflammation (nuclear and cytoplasmic nuclear factor kappa B [NFκB]) and oxidation (8‐hydroxydeoxy‐guanosine [8OHdG]). Secondary endpoints of urinary oxidation, tea polyphenol uptake in prostate tissue, and serum prostate specific antigen (PSA) were evaluated by high performance liquid chromatography and ELISA analysis. Results Ninety three patients completed the intervention. There was no significant difference in markers of proliferation, apoptosis and oxidation in RP tissue comparing GT and BT to water control. Nuclear staining of NFκB was significantly decreased in RP tissue of men consuming GT (P = 0.013) but not BT (P = 0.931) compared to water control. Tea polyphenols were detected in prostate tissue from 32 of 34 men consuming GT but not in the other groups. Evidence of a systemic antioxidant effect was observed (reduced urinary 8OHdG) only with GT consumption (P = 0.03). GT, but not BT or water, also led to a small but statistically significant decrease in serum prostate‐specific antigen (PSA) levels (P = 0.04). Conclusion Given the GT‐induced changes in NFκB and systemic oxidation, and uptake of GT polyphenols in prostate tissue, future longer‐term studies are warranted to further examine the role of GT for prostate cancer prevention and treatment, and possibly for other prostate conditions such as prostatitis. Prostate 75: 550–559, 2015. © 2014 Wiley Periodicals, Inc.